Development of a reliable path-loss model for FM broadcast reception in office locations - Marco G. Domingo; Prince Kendrick E. Estebal; Geraldine A. Tongco; Gerino P. Mappatao (Institute of Advanced Engineering and Science, 2020)
This paper proposes for the development of a path-loss model to improve the accuracy in predicting the signal level in office locations for the reception of FM broadcast. Identifying the factors that affect the signal level and eventually developing a model to predict the signal inside buildings will guide engineers in designing a broadcast system. A properly designed broadcast system will ensure optimum signal penetration in these listening areas. Further, the developed model can find applications in policy-making on the regulation of FM broadcast stations, both for analog and digital radio systems. Signal level measurements from three FM broadcast stations have been made inside eight office rooms in De La Salle University-Manila. With the three stations utilizing circularly polarized transmitting antennas, the measurements aim to determine the signal levels of the horizontal and vertical components of the received signal. These measured levels are used to determine the effects on the magnitude of the received signal of some factors, such as signal frequency and polarization, receiving antenna height, walls, transmitter-receiver distance, etc. Since the developed model is based on the measured signal levels in the actual office environment, its accuracy is then better than any of the existing models earlier developed.